Identity of Saturable Calcium-Binding Sites on Blood Platelets and Their Involvement in Platelet Aggregation - Johnston, Geoffrey I; Heptinstall, Stanley (Thrombosis and Haemostasis, 1988)
Extracellular Ca2+ ions are required for platelet aggregation and we show that they enter two platelet pools. One pool is rapidly filled and easily displaced by EGTA. The second is filled more slowly and is not displaced by EGTA. The EGTA-displaceable pool is believed to be surface-located and was found to contain at least one class of saturable binding sites as well as a class of non-saturable binding sites. The saturable sites were found to be highly selective for Ca2+ (dissociation constant, 3.5 × IO−7 M) even in the presence of 1 mM Mg2+ ions, and they took up between 261,000 and 307,000 Ca2+ ions/platelet. Full occupancy of the saturable binding sites appeared to be necessary for platelet aggregation to proceed. We also studied platelets that were unable to aggregate normally, either due to the congenital bleeding disorder Glanzmann’s thrombastenia or due to experimental manipulation. In both cases wc found decreased Ca2+uptake specifically by the saturable Ca2+ binding sites, and that this was associated with decreased number of GP IIb/IIIa molecules expressed on these platelets. We suggest that the Ca2+binding sites involved in platelet aggregation are located on the GP Ilb/IIIa complexes and may be involved in holding the glycoproteins in the complex together, and that the binding sites need to be fully occupied before aggregation can proceed.
Keywords: Extracellular calcium; Binding sites; Platelet aggregation